The Role of Midwives in Motivating Mothers to Initiate Early Breastfeeding at Pertiwi Mother and Child Hospital in Makassar City - Santi, Santi; Yufuai, Agustina R; Masding, Masding; Hanifah, Astin Nur; Yunus, Muh.; Nari, Jois; Astuti, Fanni; Wahyuni, Ria; Pannyiwi, Rahmat (International Journal of Health Sciences, 2023)
Early Initiation of Breastfeeding is a process of letting the baby crawl on its own looking for its mother's nipple immediately in the first hour after birth along with skin contact between the baby and the mother. The aim of the study was to analyze the role of midwives in motivating mothers to initiate early breastfeeding at the Makassar City Mother and Child Hospital. The research used is qualitative research. The method of data collection used is data obtained through in-depth interviews using interview guidelines and observations of the object to be studied. From the results of research conducted for approximately one month, it was found that midwives' authority in motivating mothers to carry out Early Breastfeeding Initiation is still not optimal. The implementation of exclusive breastfeeding cannot be monitored, in terms of action and motivation it is quite good because at work midwives carry out their duties with full responsibility in accordance with the midwifery code of ethics. The conclusion from the results of this study is that the role of midwives in initiating early breastfeeding still needs to be improved, because the community, especially pregnant women, are still unfamiliar with the program, so effective socialization and education is needed so that babies born can be initiated on early breastfeeding.